UPAYA PENINGKATKAN PEMAHAMAN RUMUS PADA LUAS PERMUKAAN BANGUN RUANG SISI DATAR DENGAN METODE PENGAJARAN INQUIRY DISCOVERY LEARNING DAN PEMANFAATAN MEDIA TIGA DIMENSI DI SMP NEGERI 4 SIBABANGUN - Samson Panggabean (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
See the low understanding of student learning outcomes and on subjects of mathematics focused on, whether the application of the Learning Metode of inquiry – discovery learning with three-dimensional media graphics can enhance the understanding of the students against the formula on the widespread the surface of the flat-sided room wake up on subjects of mathematics grade VIII SMP Negeri 4 even semester Sibabangun. The purpose of this class action research is to find out whether there is an increased understanding of the students against the surface area formula woke up flat-side space in the subject of mathematics the lesson using the learning metode of inquiry-discovery learning media with three-dimensional graphics. This research procedure includes twocycles where each cycle comprising planning, implementation, observation, and reflection. Class action research was conducted in the State JUNIOR 4 Sibabangun, with the object of research grade VIII totaling 42 students, consisting of 17 female students and 25 male students. The results showed that Math learning by using learning metode of inquiry-discovery learning can improve the understanding of the students against the formation of extensive formula is found waking up flat-side room with the results of the cycle I 59.04% and the cycle II 70.02%, and (2) an increase in the diprosentasekan cycle 1 to cycle 2 = 10.98%.Keywords: improve understanding of learning Media, three-dimensional graphics, metodes of inquiry-discovery learning.